2020
DOI: 10.1007/s42452-020-03401-x
|View full text |Cite
|
Sign up to set email alerts
|

Intercorrelation between physical and electrochemical behavior of nitrogen-doping in graphene for symmetric supercapacitor electrode

Abstract: Graphene and heteroatom-doped graphene are potential candidates for high-performance energy storage applications, such as supercapacitors. Herein, we have studied the structure and defect generation in nitrogen-doped reduced graphene oxide (N-rGO), synthesized via pyrolysis of urea in a wide temperature range (600-900 °C). Nitrogen-doped defect densities were analyzed in detail by the deconvolution of the Raman spectrum, where we found the importance of additional I and D'' peaks. I peak is found to be sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 63 publications
(94 reference statements)
1
28
0
Order By: Relevance
“…Hence, depending on the properties of the material, such as defects, strain, doping, crystallinity, and the number or the orientation of layers (or walls), the spectral features show a significant variation, giving rise to additional peaks like the D-band (∼1350 cm −1 ) and D′band (∼1620 cm −1 ). 1,4,7,8 Therefore, Raman spectroscopy is an essential tool in the field of carbon research, and it is wellestablished in the road map of graphite to graphene.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, depending on the properties of the material, such as defects, strain, doping, crystallinity, and the number or the orientation of layers (or walls), the spectral features show a significant variation, giving rise to additional peaks like the D-band (∼1350 cm −1 ) and D′band (∼1620 cm −1 ). 1,4,7,8 Therefore, Raman spectroscopy is an essential tool in the field of carbon research, and it is wellestablished in the road map of graphite to graphene.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a fast, simple, and nondestructive tool, Raman spectroscopy provides valuable information on the structural properties of carbon-based materials, such as fullerenes, carbon nanotubes (CNTs), and graphene and its derivatives. All these materials show some common Raman spectral features, yet the peak positions, widths, and intensities of the Raman spectra of each material have unique features to distinguish them from each other and predict their properties. , For example, the Raman spectra of sp 2 nanocarbons consist of two major features: the G-band (in the frequency range 1580–1600 cm –1 ) and the G′-band (also known as 2D-band – in the frequency range 2650–2800 cm –1 ). Hence, depending on the properties of the material, such as defects, strain, doping, crystallinity, and the number or the orientation of layers (or walls), the spectral features show a significant variation, giving rise to additional peaks like the D-band (∼1350 cm –1 ) and D′-band (∼1620 cm –1 ). ,,, Therefore, Raman spectroscopy is an essential tool in the field of carbon research, and it is well-established in the road map of graphite to graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of D and G peaks has already been well addressed in previous reports [36,37], whereas the D" peak and I peak have not been well addressed. The I peak was observed as a shoulder to the D peak, which is ascribed to the nitrogen-doped carbon structure [38] or a highly disordered carbon [39]. Particularly, an increase in nitrogen doping concentration resulted in a decrease in the calculated area of the I peak, as shown in the Supplementary Materials (Table S1).…”
Section: Raman Spectroscopy Analysismentioning
confidence: 83%
“…N-doped graphene has been comprehensively analyzed in terms of its morphology, change in electronic structure, electrocatalytic applications, and theoretical simulations. 18 , 19 Our recent works show the applicability of nitrogen-doped reduced GO (N-rGO) as an advanced supercapacitor electrode 13 and as a catalyst support material for the OER. 20 , 21 N-rGO is similar in structure to N-doped graphene, excluding the presence of a few oxygen functional groups and defects in N-rGO that are not completely removed or restored during pyrolysis at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent research work, Yadav et al explored the temperature-dependent synthesis of N-rGO, starting with natural graphite (flake size: 7 μm), and explained the structural effect on the supercapacitive behavior of N-rGO as an electric double-layer supercapacitor (EDLC). 13 In this study, the properties of N-rGO such as the degree of reduction, the extent of N-doping, formation of structural and lattice defects, specific surface area, and the crystallinity of rGO were investigated as a function of synthesis temperature. Furthermore, Hara et al demonstrated the use of N-rGO (starting from synthetic graphite, Sigma-Aldrich, flake size: < 20 μm) as the catalyst support and investigated its effect on the catalytic properties of IrO 2 nanoparticles (nps) as an electrocatalyst for the OER.…”
Section: Introductionmentioning
confidence: 99%